Cytogenetic and molecular characteristics of Atlantic eels (Anguilla anguilla and A. rostrata) genome - Salvadori S; DEIANA, ANNA MARIA; COLUCCIA, ELISABETTA; Milia A; NIEDDU, MARIELLA; PICHIRI, GIUSEPPINA; Mezzanotte R.; CAU, ANGELO; CANNAS, RITA (Italian Journal of Zoology, 1998)
The Atlantic eels, Anguilla anguilla and A. rostrata, have partially overlapping spawning sites and show incomplete reproductive isolation as testified by the presence of hybrids at low frequency. Nevertheless, significant genetic differences between the two spec-its have been pointed out by data on biochemical polymorphisms and mitochondrial DNA. This study reviews the cytogenetic and molecular data and points out differences and similarities between the two species